2020
DOI: 10.1097/brs.0000000000003898
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Matrix Rhythm Therapy in Patients with Chronic Low Back Pain

Abstract: Study Design. Randomized clinical study. Objective Our study was planned to determine the effect of matrix rhythm therapy (MRT) on pain, level of disability, and quality of life in chronic low back pain. Summary of Background Data. Low back pain is a complex and heterogeneous disorder. Different therapy options can be applied in the treatment of low back pain. In the literature, there are very few studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…A study conducted by Yurdakul etal., 24 found significant improvement in ODI score in the patient's group who used combined heat and TENS physiotherapy, the results of these studies were in line with our results and the types of physical therapy devices used in them were similar to what we employed. Özcan et al, 25 showed that disability (ODI score) was improved significantly in patients who received ten sessions of combined physical therapy (heat, TENS, US, and home exercise). As for the association between body compositions and LBP disability (ODI), we found a significant positive correlation between body fat percentage and LBP disability post physiotherapy (P = 0.013).…”
Section: Assessment Of Low Back Pain Disability Modified Oswestry Dis...mentioning
confidence: 99%
“…A study conducted by Yurdakul etal., 24 found significant improvement in ODI score in the patient's group who used combined heat and TENS physiotherapy, the results of these studies were in line with our results and the types of physical therapy devices used in them were similar to what we employed. Özcan et al, 25 showed that disability (ODI score) was improved significantly in patients who received ten sessions of combined physical therapy (heat, TENS, US, and home exercise). As for the association between body compositions and LBP disability (ODI), we found a significant positive correlation between body fat percentage and LBP disability post physiotherapy (P = 0.013).…”
Section: Assessment Of Low Back Pain Disability Modified Oswestry Dis...mentioning
confidence: 99%
“…In addition to the combine physical therapy programs, both the integrated physiotherapist programme as well as the MRT technology were shown to have a stronger effect on impairment level, life quality, and pain in people with severe back pain (3).…”
Section: Matrix Rhythm Therapymentioning
confidence: 99%
“…It also helps regulate circadian rhythm and bring the body's cells 'in harmony' [15]. The various studies on MaRhyThe® have proved its effect on pain and improved functionality in different musculoskeletal conditions [16][17][18]. But to our knowledge the effect of MaRhyThe® on neurovascular functions and plantar pressure in DPN has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%